Upaya Meningkatkan Aktivitas Dan Hasil Belajar Siswa Melalui Model Pembelajaran Snowball Throwing di SD Negeri Tanjungsari - Marni Marni (Al Hikmah: Journal of Education, 2020)
The objectives of this study are 1) To describe the learning process of the Snowball Throwing model in Mathematics learning of the Fraction Count Operation material, 2) To find out whether the Snowball Throwing model can increase the learning activities of Class VI Semester I SDN Tanjungsari students in the 2018/2019 academic year, 3 ) To find out whether the Snowball Throwing model can improve the learning outcomes of Class VI Semester I SDN Tanjungsari students in the 2018/2019 academic year. This classroom action research uses subjects and research settings for class VI semester II of the 2018/2019 academic year SD Negeri Tanjungsari, Jakenan District, Pati Regency. This classroom action research was carried out in 2 cycles of action in order to improve activities and learning outcomes of Mathematics in Counting Fractions Operations. In the initial condition, the student learning outcomes showed that of the 26 students there were only 12 students or 33% who had finished learning, while 24 students or 67% had not finished learning. The results showed that in the first cycle the learning process obtained an average score of 2.63 in the sufficient category, the students' learning activities in the first cycle had an average score of 69 in the sufficient category, and the student learning outcomes in the first cycle showed that there were 36 students. 26 students or 72% have completed the KKM while 10 students or 28% have not completed the KKM with an average score of 74. In the second cycle the learning process increased, namely the average score became 3.32 with the very good category, student learning activities increased to 88 with a good category, while the learning outcomes of students who completed learning were 33 students or 92%, while those who had not finished learning were only 3 students or 8% with an average score of 89.Tujuan dari penelitian ini yaitu: 1) Untuk mendeskripsikan proses pembelajaran model Snowball Throwing pada pembelajaran Matematika materi Operasi Hitung Pecahan, 2) Untuk mengetahui apakah melalui model Snowball Throwing dapat meningkatkan Aktivitas belajar siswa Kelas VI Semester I SDN Tanjungsari tahun pelajaran 2018/2019, 3) Untuk mengetahui apakah melalui model Snowball Throwing dapat meningkatkan hasil belajar siswa Kelas VI Semester I SDN Tanjungsari tahun pelajaran 2018/2019. Penelitian tindakan kelas ini menggunakan subyek dan setting penelitian kelas VI semester II Tahun Pelajaran 2018/2019 SD Negeri Tanjungsari  Kecamatan Jakenan Kabupaten Pati. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus tindakan dalam rangka meningkatkan aktivitas dan hasil belajar Matematika materi Operasi Hitung Pecahan. Pada kondisi awal hasil belajar siswa menunjukkan bahwa dari 26 siswa hanya terdapat 12 siswa atau 33% yang tuntas belajar, sedangkan 24 siswa atau 67% belum tuntas belajar.  Hasil penelitian menunjukkan bahwa pada siklus I proses pembelajaran memperoleh nilai rata 2,63 dengan kategori cukup, Aktivitas belajar siswa pada siklus I mendapatkan hasil nilai rata-rata yaitu 69 dengan kategori cukup, dan hasil belajar siswa pada siklus I menjunjukkan bahwa dari 36 siswa terdapat 26 siswa atau 72% tuntas KKM sedangkan 10 siswa atau 28% belum tuntas KKM dengan nilai rata-rata 74. Pada siklus II proses belajar pembelajaran meningkat yaitu nilaii rata-rata menjadi 3,32 dengan kategori sangat baik, Aktivitas belajar siswa meningkat menjadi 88 dengan kategori baik, sedangkan hasil belajar siswa yang tuntas belajar sebanyak 33 siswa atau 92%, sedangkan yang belum tuntas belajar hanya 3 siswa atau 8% dengan nilai rata-rata 89.